SLAMF8 Downregulates Mouse Macrophage Microbicidal Mechanisms via PI3K Pathways - Romero-Pinedo, Salvador; Barros, Domingo I. Rojas; Ruiz-Magaña, María José; Maganto-García, Elena; Moreno de Lara, Laura; Abadía-Molina, Francisco; Terhorst, Cox; Abadía-Molina, Ana C. (Frontiers in Immunology, 2022)
Signaling lymphocytic activation molecule family 8 (SLAMF8) is involved in the negative modulation of NADPH oxidase activation. However, the impact of SLAMF8 of this downregulation on macrophage functionality and the microbicide mechanism remain elusive. To study that in depth, we first analyzed NADPH oxidase activation pathways in wild type and SLAMF8 deficient macrophages upon different stimulus. Here in, we describe increased phosphorylation of the Erk1/2 and p38 MAP Kinases, as well as increased phosphorylation of NADPH oxidase subunits in SLAMF8 deficient macrophages. Furthermore, using specific inhibitors, we observed that specific PI3K inhibition subsided the differences observed between wild type and SLAMF8 deficient macrophages, either stimulated with PMA, LPS or Salmonella typhimurium infection. Consequently, SLAMF8-deficient macrophages also showed increased recruitment of small GTPases such as, Rab5 and Rab7, and the p47phox subunit to cytoplasmic Salmonella, suggesting an impairment of Salmonella-containing vacuole (SCV) progression in SLAMF8 deficient macrophages. Enhanced iNOS activation, NO production, and IL-6 expression were also observed in the absence of SLAMF8 upon Salmonella infection, either in vivo or in vitro, whiles overexpression of SLAMF8 in RAW264.7 macrophages showed the opposite phenotype. In addition, SLAMF8-deficient macrophages showed increased activation of Src kinases and reduced SHP-1 phosphate levels upon IFN and Salmonella stimuli in comparison to wild type macrophages. In agreement with in vitro results, Salmonella clearance was augmented in SLAMF8-deficient mice compared to that in wild-type mice. Therefore, in conclusion, SLAMF8 intervention upon bacterial infection downregulates mouse macrophage activation, and confirmed that SLAMF8 receptor could be a potential therapeutic target for the treatment of severe or unresolved inflammatory conditions.